Analysis the Conceptual Understanding Level and Understanding Model of Pre-Service Physics Teacher - Hendri Saputra; Dona Mustika (Jurnal Penelitian Pendidikan IPA, 2022)
Understanding in physics concept is needed to solve the problem in life. the aim of this research was to analyze the students’ level of conceptual understanding level and students’ model of understanding. It will help educators in selecting the suitable teaching approaches and strategies to gain conceptual understanding. This research design used a quantitative-descriptive model. The design aims to describe the conceptual understanding level of pre service teacher on Newton’s Laws concept. The subjects were 40 students of Physics Education Department UNSAM who credited Fundamental of Physics course. Analysis conceptual understanding level and understanding model of pre-service physics teacher used instrument test which developed by Saglam. This research show that the students’ level of understanding (pre-service physics teacher, UNSAM) was vary about Newton’s law concepts but show the insignificant numbers among levels. Generally, students’ achievement has no fallen progressively. It explains, students reach different success in the questions about conceptual understanding. While students’ understanding models, they most appear in theoretical model (TM) and inappropriate model (IM). This result support the improvement of pre-service physics teachers’ conceptual understanding